THE DEVELOPMENT STRATEGY OF BAMBOO CRAFT HOME-SCALE INDUSTRIES USING DIAMOND PORTER MODELING AT MALUMBI VILAGE, KAMBERA DISTRICT, EASTERN OF SUMBA REGENCY: SWOT Analysis - Taru, Nikodemus Samuel; Mary Prihtanti, Tinjung; Nuswantara, Bayu (Jurnal AGRISEP, 2023)
The existence of Malumbi Vilage as bamboo craft production area predicted has a chance to be developed. The aim of this study was treated the SWOT analysis against the bamboo craft business using SWOT matrix and Diamond Porter Modeling to determine the suitable strategy developing priority of the business. Results of scoring from internal aspect (IFE) showed that the bamboo craft business has strength from the skills of the craftsmans with score 0.36 and the weakness showed from the age of craftsmans, marketing targets and information acquisition with each scores showed 0.12. Total score of overall internal aspect (IFE) showed 2.79 higher than standard 2.5 mean that the bamboo craft business from Malumbi already success maintenancing the strength to handling the weakness side. While the scoring results from external aspects (EFE) of the bamboo craft has the prime opportunity from the continuity availiability of the raw material swith score 0.46 while the main threats were the existence of competitors and the unstable of economical conditions with the score of each showed 0,35. Score of overall external aspect (EFE) showed 2.88 higher than standard 2.5 mean that the bamboo craft business able to advantaging the opportunities to covering the threats. Based on total score of IFE 2.79 and EFE 2.88 then matching the scores using SWOT matrix and Diamond Porter Modeling then concluded that this bomboo craft business stay in middle level of external and internal conditions then in this condition the suitable strategies to applied was “Grow and Develop” strategy.